2000
DOI: 10.1128/iai.68.3.1054-1060.2000
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Production of Local Immunoglobulin A toPneumocystis cariniiin Bronchoalveolar Lavage Fluid from Human Immunodeficiency Virus-Positive Patients

Abstract: An enzyme-linked immunosorbent assay and a Western blot analysis were developed to study the antibody response to Pneumocystis carinii in serum and bronchoalveolar lavage fluid from 27 human immunodeficiency virus 27 (HIV)-infected patients with P. carinii pneumonia (Pcp), 32 patients without Pcp, and 51 HIV-negative controls. Urea was used for the correct dilution of epithelial lining fluid, and albumin was used to evaluate transudation from plasma for the assessment of local production of antibodies to P. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…These results support the concept of a role for IgA-mediated protection from Pneumocystis colonization and are consistent with clinical studies that showed mucosal antibodies to Pneumocystis are decreased in patients with PcP compared to HIV ϩ patients without PcP or with HIV-negative controls (27,31).…”
Section: Test) (D) Monkeys That Remained Pcsupporting
confidence: 79%
“…These results support the concept of a role for IgA-mediated protection from Pneumocystis colonization and are consistent with clinical studies that showed mucosal antibodies to Pneumocystis are decreased in patients with PcP compared to HIV ϩ patients without PcP or with HIV-negative controls (27,31).…”
Section: Test) (D) Monkeys That Remained Pcsupporting
confidence: 79%
“…Those with current PCP experienced lower BALF antibody responses to Msg compared to those without a current diagnosis of PCP, similar to previously reported findings [ 30 ]. The mechanisms for lower IgA responses to Msg in HIV-infected patients with PCP are unclear.…”
Section: Discussionsupporting
confidence: 90%
“…jirovecii and what clinical and environmental factors drive these responses [3, 30, 31]. Tobacco smoking and ambient air pollution may influence PCP presentation and serum antibody responses to P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the majority of studies regarding PJP, both in HIV-positive and HIV-negative patients, an elevation in serum LDH concentration is a sign, although non-specific, that helps diagnostic confirmation and it is an important negative prognostic factor, since LDH elevation is a marker of cellular necrosis and an indicator of poor tissue perfusion. [42][43][44][45][46][47] Although literature has reported serum IgG deficit only as a predisposing factor for PJP in HIVpositive patients, [48][49][50][51][52] IgG role as opsonizing molecules and enhancer of macrophages respiratory burst (as already mentioned) may account for the worst observed prognosis in the group of patients with a lower mean serum IgG concentration. It is interesting to note that our patients mean serum procalcitonin concentration was 6.24±10.66 ng/mL, way too high to be related to a fungal infection in general and PJP in particular (PCT is usually below 2 ng/mL): this laboratory finding can be explained by some patients positivity to BAL microscopic examination, hemocultures and urinary antigens for Gram + and Grambacteria.…”
Section: Discussionmentioning
confidence: 99%